(untitled) (Journal of Comparative & International Higher Education, 2022)
This study investigates the relationship between Facebook use and acculturation using Berry’s acculturation model and Communication Accommodation Theory (CAT) as theoretical frameworks. Seventeen first or second semester international students participated in an online survey. The data were gathered through online pre-/and post-surveys as well as observations of the international students’ Facebook wall postings. Fifteen students shared their Facebook wall postings. The major findings of this study include: a) the pattern of Facebook postings was the same during the semester, b) international students used convergence communication strategies to better communicate with people in their network, and c) some participants’ Facebook postings indicate a strong identification with their native culture.